2015
DOI: 10.1590/0001-3765201520140220
|View full text |Cite
|
Sign up to set email alerts
|

Use of dried waste of cassava starch extraction for feeding lactating cows

Abstract: The aim of this study was to determine the best level of utilization of dried waste of cassava starch extraction (WCSEd) as a substitute for corn for lactating cows. Four lactating cows were fed diets with increasing levels (0%, 33%, 66% and 100%) of WCSEd as a substitute for corn. The intake and digestibility of dry matter and nutrients, milk production and composition, blood parameters of glucose and urea and microbial synthesis of the diets were evaluated. There was a reduction in dry matter intake, organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…These results corroborate with those presented by Fernandes et al (2015), in which cows fed with corn-based animal feed showed a higher intake of 10.27% compared to those that were fed with rations based on WCSEd. The reduction of intake may be associated with increased levels of NDF in diet, since the period for feeding the animals was limited to 8 hours a day, increasing the effect of NDF on ingestion (SILVA, 2011).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These results corroborate with those presented by Fernandes et al (2015), in which cows fed with corn-based animal feed showed a higher intake of 10.27% compared to those that were fed with rations based on WCSEd. The reduction of intake may be associated with increased levels of NDF in diet, since the period for feeding the animals was limited to 8 hours a day, increasing the effect of NDF on ingestion (SILVA, 2011).…”
Section: Resultssupporting
confidence: 91%
“…The reduction of intake may be associated with increased levels of NDF in diet, since the period for feeding the animals was limited to 8 hours a day, increasing the effect of NDF on ingestion (SILVA, 2011). The DM intake as a percentage of BW was not influenced by diet, corroborating with the effects observed by Fernandes et al (2015), using the wet residue of cassava in place of maize, in the feeding of lactating cows. The animals showed no weight gain throughout the experiment.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…One study demonstrated that dried residue after starch extraction could be used to feed dairy cows at around 100 days of lactation to replace more than 100% of corn [ 10 ]. One study showed that fermented cassava residue can be used as an energy source for beef cattle without impacting the digestibility as well as growth and meat performance [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The conservation of this residue is hampered by its high levels of humidity (85%) (Abrahão et al, 2006). The drying of this byproduct would enable its proper conservation and transport, but raise the costs of acquisition (Fernandes et al, 2015). On 2015, Brazil produced 750 thousand tons of cassava starch (Associação Brasileira dos Produtores de Amido de Mandioca, 2018).…”
Section: Introductionmentioning
confidence: 99%